From E-Government to Digital Transformation: Leadership - Cuya, Miguel (2021)
In these times of pandemic, the world has witnessed the power of connectivity, and many organizations have seen the need to rethink their models and even reinvent themselves in response to this new form of global connectivity. This transformation has also changed the way public organizations deliver services to citizens. Successfully driving the digital transformation process requires a leader with skills and knowledge. Leadership has been considered as a critical factor that impacts e-government. This paper presents the competences of those responsible for driving digital transformation (DT) in organizations. The results show that leadership is one of the most desired competences followed by technological knowledge, business vision, and customer orientation. These aspects must be considered as a fundamental basis, in any organization that takes on the challenge of this paradigm shift.